2011
DOI: 10.1007/s00442-011-2013-1
|View full text |Cite
|
Sign up to set email alerts
|

Competition–colonization trade-offs in a ciliate model community

Abstract: There is considerable theoretical evidence that a trade-off between competitive and colonization ability enables species coexistence. However, empirical studies testing for the presence of a competition–colonization (CC) trade-off and its importance for species coexistence have found mixed results. In a microcosm experiment, we looked for a CC trade-off in a community of six benthic ciliate species. For each species, we measured the time needed to actively disperse to and colonize an empty microcosm. By measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Although all of the five ciliate species consumed the algal resource, final abundances of the algae were (marginally) negatively correlated only with abundances of Onychodromopsis . A previous experiment showed that among the five ciliate species Onychodromopsis had by far the highest carrying capacity, at least twice as high as that of any of the other species [17]. Accordingly, total ciliate abundance in the present experiment was strongly positively correlated with abundance of Onychodromopsis .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although all of the five ciliate species consumed the algal resource, final abundances of the algae were (marginally) negatively correlated only with abundances of Onychodromopsis . A previous experiment showed that among the five ciliate species Onychodromopsis had by far the highest carrying capacity, at least twice as high as that of any of the other species [17]. Accordingly, total ciliate abundance in the present experiment was strongly positively correlated with abundance of Onychodromopsis .…”
Section: Discussionsupporting
confidence: 64%
“…S3B). In contrast to Onychodromopsis , Paramecium had a high colonization ability, based on an intermediate growth rate and a very high dispersal rate [17]. These traits enabled Paramecium to quickly reach all basins even with low connectivity, although the species was initially absent from more patches than Onychodromopsis .…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of both stable and fluctuating microenvironments should both select for and permit the coexistence of both fast and slow life history phenotypes within the same tumor 36 . Tradeoffs between quick colonization (i.e., rapid division and migration into areas of unutilized resources) and effective competition (i.e., investment in survival) have been associated with coexistence and the evolution of slow and fast life histories in some ciliate protists 40 . While heterogeneity in blood flow is the most obvious source of variations in extrinsic mortality and resources, other factors such as immune response, fibroblast infiltration and hormone or growth factor availability may further contribute to divergent selective forces on the life history phenotypes of neoplastic cells.…”
Section: Tumor Heterogeneitymentioning
confidence: 99%
“…Despite a general acceptance of the theoretical framework, to our knowledge there is no direct experimental treatment of the general predictions of the CC theory; in fact, indirect tests that attempted to document the existence of the CC trade-off have produced contradictory results in experimental [10][11][12][13] and observational studies of natural species assemblages [14][15][16][17][18] . Moreover, because the existence of a CC trade-off in an assemblage does not necessarily indicate that CC dynamics are determinant, indirect approaches have limited power to evaluate the theory.…”
mentioning
confidence: 99%